Akibat Hukum Jual Beli Tanah Dan Bangunan Oleh Penjual Yang Sakit Stroke - Pangesti, Shinta; Kusnadi, Felicia (Program Studi Magister Kenotariatan Fakultas Hukum UNTAG Semarang, 2024)
The transfer of land ownership is often done through sales and purchases. People who are under guardianship may also do the transaction through specific procedures that have been regulated in Indonesia. This research aims to answer the two problem formulations raised, namely what are the requirements for the sale and purchase of land and buildings by sellers who are under guardianship due to a stroke based on the laws and regulations in Indonesia and what are the legal consequences of buying and selling land and buildings by sellers who are suffering from a stroke (Case Study of Supreme Court Decision Number 3586 K/Pdt/2020)? This normative-empirical legal research uses a law and case approach by obtaining data through literature studies and interviews. A seller who is under guardianship due to a stroke must have a court determination regarding guardianship and the appointment of a curator to represent him in carrying out legal acts of buying and selling land and buildings. Because the seller who was suffering from a stroke in the case study was not proven to be incompetent, the Sale and Purchase Deed was legally valid.